Posttraumatic growth and cognitive and emotional processing from disclosure in the aftermath of a traumatic event - Teixeira, Catarina (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. Monte da Caparica, Portugal, 20-22 June 2018